Ulcerative oral lesions: an overview of non-pharmacologic treatment options - Veneri, Federica; Filippini, Tommaso; Bellini, Pierantonio; Consolo, Ugo; Generali, Luigi (Acta Biomedica Atenei Parmensis, 2024)
Background and Objective: Ulcerative diseases frequently affect the oral cavity and are disabling conditions. The management is challenging, and traditional treatments are associated with potential side effects. Alternative non-pharmacologic strategies have become available to effectively manage these conditions. This review aims at providing a synthesis of the most common erosive-ulcerative oral diseases and an updated overview of the main non-pharmacologic options for their management, such as laser therapy, ozone applications, and photodynamic therapy. Methods: A narrative review was conducted by searching PubMed/MEDLINE for the most recent relevant systematic reviews or, alternatively, clinical trials or case reports. Results: Laser photobiomodulation therapy (PBMT), ozone therapy and photodynamic therapy (PDT) generally resulted in rapid relief of painful symptoms, reduced healing time and improved oral functions and patients’ quality of life. No major side-effects were reported. Regardless of the primary etiology, photodynamic therapy proved particularly effective in case of infections. Ozone was used in gaseous, ozonized water and oil formulations. The most used light sources were Nd:YAG, He:Ne, Er,Cr:YSGG, red and infrared diode lasers and LED for PBMT, while red diode lasers prevailed for PDT. The most common photosensitizers were methylene blue and toluidine blue O. Conclusions: There is growing evidence for an efficacy of PBMT, ozone and PDT for the treatment of ulcerative oral lesions, and therefore these approaches should be considered as valid non-pharmacologic strategies. However, due to the great heterogeneity of protocols, additional well-designed research to identify the best therapeutic protocols is needed.